Development of metric characters of children from Great Poland - Ćwirko-Godycki, Michał (Anthropological Review, 1975)
The author presents results of statistical treatment of metrical characters of school children examined longitudinaly in years 1947 - 1953. These examinations were initiated by the author and carried under his guidance in all kindergartens and primary schools of Poznań voivodeship in first ten days of June each year.